HUBUNGAN ANTARA CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA KEUANGAN INDUSTRI KEUANGAN SYARIAH DI INDONESIA - Dewi Rosarina Rosidi Putri; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2014)
The aim of this study is to analyze the influence of CSR Disclosure on financial performance of companies in the next year. Financial Performance ratios which are used in this study are ROA and ROE. The population consists of all Islamic based companies which are included in Islamic Financial Industry, such as Islamic Financing Companies, Islamic Insurance Company, and Islamic Banking. The sampling method is puposive sampling and the finale amounts of the sample are 11 Islamic Bankings and 1 Islamic Financing Company. Linear Regression is used in this study in order to analyze the data. The results of this study indicate that CSR Disclosure has positively significant influence on ROE. On the other hand, CSR Disclosure doesn’t have a significant influence on ROA.